Review of dielectric drying of foods and agricultural products - Wang, Yunyang; Li, Yuanrui; Wang, Shaojin; Zhang, Li; Gao, Mengxiang; Tang, Juming (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: Dielectric drying methods with microwave (MW) and radio frequency (RF) energy as emerging drying technologies have drawn much attention from both research community and industry over the past decades. When properly applied, MW and RF drying can be energy efficient and of great potential to be used for a wide range of materials. However there are few reviews that cover both MW and RF drying technologies. Such a review is timely considering the ever increasing interest of the food industry in adapting energy efficient new drying technologies. This paper attends to provide a comprehensive review on uses of MW and RF energy in drying of foods and agricultural products. It provides a brief discussion on the fundamental theory of MW and RF heating and gives a general overview of the works of the most active research groups on modeling of drying kinetic, energy control strategy and the influence of MW and RF drying conditions on quality and structural changes of the final products. Finally, it proposes possible solutions to main challenges facing the industrial adaptation of the technologies and makes suggestions on further research directions to improve the dielectric drying. Keywords: dielectric drying, foods, agricultural products, microwave, RF energy DOI: 10.3965/j.issn.1934-6344.2011.01.001-019 Citation: Wang Yunyang, Li Yuanrui, Wang Shaojin, Zhang Li, Gao Mengxiang, Tang Juming. Review of dielectric drying of foods and agricultural products. Int J Agric & Biol Eng, 2011; 4(1): 1<span style="font-size: 9pt; line-height: 140%; font-family: